La pintura como estrategia didáctica para una formación integral (2022)
This research entitled "Painting as a didactic strategy for comprehensive training", sought to propose significant experiences to students that lead them to discover the close relationship between knowledge and painting; helping to awaken their creativity, interest, multiple intelligences and the agility to create individual and collective knowledge through a good process and projection in the different areas of knowledge, where all the elements that enrich the word "Art" can be recognized. from the strategy of "Painting". That is why the general objective is based on proposing painting as a didactic strategy, for the integral formation of the 2nd year students of the I.E.E. Superior Normal Our Lady of Fátima de Sabanagrande – Atlantic. This research work has a qualitative approach and a phenomenological design to carry out its implementation. From this, the techniques for data collection and results to be used are direct observation, interviews and surveys, which will be enriched by different instruments such as conducting an interview format, the use of the field diary (Ficha of observation), a brief questionnaire to the students and contributions of technological elements (cameras-voice recorder). The results obtained from the activities implemented at grade 2°C show that the students are more motivated to learn from a didactic strategy in which they use colors and paints; giving way to express themselves in a better way, to seek multiple solutions in their environment and simultaneous help with their classmates. In addition, it was possible to work from the authors and theories that support this project.